ANALYSIS OF THE INFLUENCE OF E-SERVICE QUALITY AND PERCEIVED RISK ON CUSTOMER LOYALTY - Darodjatun, M.A.S Sridjoko; Prambudi, Bono; Mubais, Ahmad; Sarimaryoni, Hamdi; Gunawan, Ikhsan; Imron, Moch (LP2M Universitas Bina Bangsa, 2025)
This research aims to analyze the influence of electronic service quality (e-service quality) and risk perception on customer loyalty at the Indah Cargo Logistik Jepara Branch delivery service. The research method used is a survey with a quantitative approach. The research sample of 100 respondents was obtained through accidental sampling technique. Data analysis uses multiple linear regression. The research results show that both e-service quality and risk perception significantly and positively influence customer loyalty. Good electronic service quality and low risk perception encourage customers to be more loyal to Indah Cargo Logistik delivery services. The coefficient of determination (R²) of 0.724 indicates that 72.4% of the variation in customer loyalty can be explained by the e-service quality and risk perception variables. This means that these two variables have a fairly strong influence on customer loyalty. The remaining 27.6% of variations in customer loyalty are influenced by other factors not measured in this research